Multiple high-risk human papillomavirus infections exacerbate cervical lesion risk: epidemiological evidence from suining, Sichuan - Yaling Jing; Jianhui Chen; Fang Lin; Xiaonan Huang; Yulin Liu; Mingcai Zhao; Chuan Ye; Lianfang Zhao; Xiaofang Liu; Jiayan Yang (Virology Journal)
Abstract Background Studies on the pathogenicity of single and multiple human papillomavirus (HPV) infections have reported inconsistent results. Moreover, no data on HPV epidemiology in the Suining region of China have been published. Methods Cervical samples were collected from women undergoing gynecological examinations at the Suining Central Hospital. Fluorescent polymerase chain reaction (PCR) was used for HPV genotyping, and cytological and pathological examinations were performed to analyze the correlation between the infection patterns of high-risk HPV types (single vs. multiple infections) and cervical lesions. Results The most prevalent high-risk HPV types were HPV52, 58, 16, 53, and 51. The proportion of disease cases (cervical intraepithelial neoplasia or cervical cancer) in multiple infection groups (720/1,550) was significantly higher than that in single infection groups (2,109/6,498) (relative risk = 1.43, 95% confidence interval = 1.34–1.53, p < 0.001). A positive correlation was observed between the number of HPV infections and the proportion of disease cases (r = 0.839, p = 0.009). Conclusion Multiple HPV infections were significantly associated with more severe cervical lesions, and a higher infection multiplicity correlated with an increased pathogenic risk. Our findings support that multiple HPV infections significantly elevate cervical lesion risk, providing a basis for referring such patients to further examination.